2011
DOI: 10.1063/1.3675802
|View full text |Cite
|
Sign up to set email alerts
|

Whispering gallery modes for elastic waves in disk resonators

Abstract: The resonant modes of elastic waves in disk resonators are computationally studied with the finite difference time domain method. Different materials examined for the disk such as platinum and silicon. The effect of a glass substrate is also important especially in the case of silicon disks because of the similarity of sound velocities and mass densities between the two materials. The possibility of using those structures as sensors is also considered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Recent studies report the potentiality of these modes in the field of PC. Li et al [30] immersed an isolated tube in liquid medium and showed that WGMs can exhibit a narrow periodic transmission dip with a high quality factor, while Kaproulias and Sigalas [31] considered the disk geometry for sensing application. The main recent interest in WGMs is related to the excitation of acoustic modes in optical WGM resonators via backward stimulated Brillouin scattering (SBS) [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies report the potentiality of these modes in the field of PC. Li et al [30] immersed an isolated tube in liquid medium and showed that WGMs can exhibit a narrow periodic transmission dip with a high quality factor, while Kaproulias and Sigalas [31] considered the disk geometry for sensing application. The main recent interest in WGMs is related to the excitation of acoustic modes in optical WGM resonators via backward stimulated Brillouin scattering (SBS) [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…WGM resonators have been presented in shapes such as discs [11], toroids [12], and spheres [13,14]. This paper deals with a new design that was originally made to perform as a strain gauge.…”
Section: Methodsmentioning
confidence: 99%
“…The work on the hollow pillars in the field of acoustics dates back to the 1910s [22]. Taking into account the fact that hollow pillars can play a very significant role in optical or acoustic high Q resonators [23,24], recent studies report the potentiality of the hollow pillars in the field of photonic and phononic crystals [25][26][27][28]. Jin et al [29] theoretically demonstrate a homogeneous silicon plate with a square array of hollow pillars deposited on one side and discuss some features of the hollow pillars in both Bragg and low frequency gaps for wavelength division in multiplexer devices.…”
Section: Introductionmentioning
confidence: 99%